2002
DOI: 10.1016/s0378-1097(02)00470-6
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and type 2 responses to Leishmania major

Abstract: Leishmania major is a protozoan parasite that is transmitted to the mammalian host by its sand fly vector when the fly probes in the host's skin for a blood meal and injects the parasite within its saliva. In mice experimentally infected with L. major, outgrowth of CD4 type 1 (Th1) cells leads to resolution of the infection, but outgrowth of type 2 (Th2) cells exacerbates disease. To design an effective vaccine against the parasite (and other pathogens that induce polarized Th1 and Th2 responses), we must dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 30 publications
1
56
0
11
Order By: Relevance
“…It was also shown that the CD28/ CD80-CD86 interaction on neutrophil/macrophages induces IFN-␥ production, restricting the growth of L. major (44). Importantly, the mechanisms leading to cure and resistance to Leishmania infection are associated with macrophage activation, resulting from TNF-␣-and IFN-␥-induced production of free radicals and ultimately with destruction of the intracellular parasites (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the CD28/ CD80-CD86 interaction on neutrophil/macrophages induces IFN-␥ production, restricting the growth of L. major (44). Importantly, the mechanisms leading to cure and resistance to Leishmania infection are associated with macrophage activation, resulting from TNF-␣-and IFN-␥-induced production of free radicals and ultimately with destruction of the intracellular parasites (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous leishmaniasis laboratory mouse model using C57BL/6 (resistant) and BALB/c (susceptible) infected with L. major is the most employed system for analyzing the regulation of the immune response against this pathogen only contained by a cell-mediated response 19,30 . However, C57BL/6 mice inoculated with L. (L.) mexicana developed a chronic disease 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The inability of macrophages to kill the parasite is a result of the parasite's longreported capacity in skewing the host immune response toward a disease-promoting Th2 phenotype that consequently suppresses host-protective Th1 phenotype (15,16). To execute this, Leishmania needs specific molecules that are secreted by Leishmania itself or it may activate macrophages to produce immunosuppressive molecules that render the macrophage defense inactive.…”
mentioning
confidence: 99%